Using Remote Sensing Techniques to Assess Land Use/Land Cover Change in Laylan Sub-District, Kirkuk Province, Iraq - Mahmood, Faleh; Ali, Aras (Iraqi Journal of Science, 2023)
In this study, Landsat (Thematic Mapper) TM and enhancement Thematic Mapper plus) ETM+ images obtained in 1990, 2000, and 2006 were used to Assess land use/land cover (LULC) changes in Laylan sub-district, Kirkuk province, Iraq, using Supervised Maximum Likelihood classification (MLC) ) methods. Aerial photographs, digital LULC maps, and topographic maps were utilized to assess classification accuracy. The aim of this study is to identify the changes that have occurred in land use in the city through different periods of time. Objective of the study is also to identify the factors affecting the distribution uses of land in the city. Five different land cover/use categories have been used, named Vegetation, sand, soil, salt soil, urban areas. The classifications showed that decrease of the grasslands areas, agricultural lands and vegetation in general and the increase of urban areas mixed soil. The results are being used to project future analyze landscape diversity and fragmentation, and examine different scenarios for more ecological management. The classifications have provided an economical and accurate way to quantify, map and analyze changes over time in land cover.